Teachers and Education Personnel’s Efforts in Madrasah Branding to Increase the Attractiveness of New Student Admissions in the Digital Era - Majid, Lukman Abdul; Bunayar, Bunayar; Purwanto, Agus Joko; Yusuf, Arifin; Asy’arie, Bima Fandi (STIT Ahlussunnah Bukittinggi, 2025)
This stuaThis study aims to determine the efforts of teachers and educational staff in branding madrasahs to increase the attractiveness of new student admissions in the digital era. Then, this study also analyzes the supporting and inhibiting factors in the madrasah branding process. The method employed is field research, utilizing a case study approach and a qualitative methodology. The research focus was conducted at Madrasah Aliyah Daar Al-Hikmah Seputih Mataram, Central Lampung. Based on the findings from a total of 25 informants, madrasah branding is a crucial strategy for attracting the interest of the community and prospective new students, particularly in today's digital landscape. Several strategic steps implemented include the creation of an official website as a public information medium, the formation of a branding team consisting of competent teachers and education staff, the use of social media such as Instagram and TikTok to creatively showcase various madrasah activities, community and alums involvement, and regular evaluations are important steps in expanding the promotional reach and improving the branding. In addition, several key supporting factors in madrasah branding include the presence of skilled human resources in digital design and communication, as well as the need for public trust in the madrasah due to its religious foundation. On the other hand, challenges faced by madrasah branding include budget constraints, competition between educational institutions (such as schools and Madrasah), and a lack of market understanding. Therefore, to achieve optimal branding effectiveness, Madrasah must collaborate, innovate, and continually improve their capacity to adapt to changing times and community needsdy aims to determine the efforts of teachers and educational staff in branding madrasahs to increase the attractiveness of new student admissions in the digital era. Then, this study also analyzes the supporting and inhibiting factors in the madrasah branding process. The method employed is field research, utilizing a case study approach and a qualitative methodology. The research focus was conducted at Madrasah Aliyah Daar Al-Hikmah Seputih Mataram, Central Lampung. Based on the findings from a total of 25 informants, madrasah branding is a crucial strategy for attracting the interest of the community and prospective new students, particularly in today's digital landscape. Several strategic steps implemented include the creation of an official website as a public information medium, the formation of a branding team consisting of competent teachers and education staff, the use of social media such as Instagram and TikTok to creatively showcase various madrasah activities, community and alums involvement, and regular evaluations are important steps in expanding the promotional reach and improving the branding. In addition, several key supporting factors in madrasah branding include the presence of skilled human resources in digital design and communication, as well as the need for public trust in the madrasah due to its religious foundation. On the other hand, challenges faced by madrasah branding include budget constraints, competition between educational institutions (such as schools and madrasas), and a lack of market understanding. Therefore, to achieve optimal branding effectiveness, madrasas must collaborate, innovate, and continually improve their capacity to adapt to changing times and community needs